Wombstone-massive calcified fibroid: a case report - Ananthula, Shruthi; Gopalan, Ushadevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
We report a case of a calcified submucous leiomyoma in 50 years women with lower abdominal discomfort. She had no previous history of surgery. Work up confirmed a calcified leiomyoma. The diagnosis was made by radiological findings. Total abdominal hysterectomy with bilateral salpingo-oophorectomy is the surgery of choice for these cases. Histopathological examination confirmed a calcified leiomyoma. A calcified leiomyoma in a post-menopausal woman is rare.